2016
DOI: 10.1108/bfj-03-2015-0097
|View full text |Cite
|
Sign up to set email alerts
|

The Mexican consumer, reluctant or receptive to new foods?

Abstract: Purpose – The purpose of this paper is to measure the relative degree of rejection or reluctance to try new foods of the Mexican consumers. Design/methodology/approach – To measure the degree of acceptance or rejection that individuals have for foods that are unusual in their diets, a phobia scale was used to new foods developed by Pliner and Hobden (1992) Food Neophobia Scale (FNS). The authors also distinguished between individuals’ pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
8
0
6
Order By: Relevance
“…This value is acceptable in exploratory research (Hair et al, 2010). Salgado et al (2016) (Tuorila, Lahteenmaki, Pohjalainen, & Lotti, 2001). In contrast, other authors have reported that there are no differences in the level of food neophobia regarding this variable (Choe & Cho, 2011;Fernandez-Ruiz et al, 2013;Zhao et al, 2020).…”
Section: Food Neophobia Scalementioning
confidence: 77%
See 4 more Smart Citations
“…This value is acceptable in exploratory research (Hair et al, 2010). Salgado et al (2016) (Tuorila, Lahteenmaki, Pohjalainen, & Lotti, 2001). In contrast, other authors have reported that there are no differences in the level of food neophobia regarding this variable (Choe & Cho, 2011;Fernandez-Ruiz et al, 2013;Zhao et al, 2020).…”
Section: Food Neophobia Scalementioning
confidence: 77%
“…The second part of the questionnaire was based on FNS (Pliner & Hobden, 1992), which is composed of 10 items that assess the degree of willingness or rejection to try new or unfamiliar foods among consumers. Generally, the items are assessed on a Likert scale from five to seven points, while at least five sentences of scale must be reversed for their analysis (Salgado et al, 2016) (Table 2). Some authors use the term "ethnic food" in the FNS to measure the intention or rejection for foods that have been introduced to new consumer markets where the population is unfamiliar with them (Choe & Cho, 2011).…”
Section: Food Neophobia Scalementioning
confidence: 99%
See 3 more Smart Citations